Patient’s Quality of Life After 3-and 6-Months Cataract Surgery - Juanarta, Pieter; Karfiati, Feti; Budiman, Budiman (Faculty of Medicine, Universitas Padjadjaran, 2024)
Cataract surgery is the most common elective procedure and has been shown to increase patients' visual acuity. However, visual acuity alone cannot adequately represent their quality of life. Quality of life can be measured with a standardized questionnaire, such as the National Eye Institute Refractive Error Quality of Life Instrument. Patients with better quality of life pre-operatively will benefit less from cataract surgery. This study aimed to describe patients' quality of life after long-term cataract surgery in the National Eye Center Cicendo Eye Hospital. This cross-sectional descriptive study used primary data collected using a questionnaire from March to May 2022. The subjects were 33 people with cataracts who underwent uncomplicated cataract surgery at Cicendo National Eye Hospital over the past three and six months of the study. Patients who met the inclusion criteria were given the NEI-RQL 42 questionnaire. In visual clarity, patient expectations, near vision, far vision, daily fluctuations, activity limitations, suboptimal correction, and satisfaction with correction variables, an increase in value at three months was observed, yet slightly decreased at 6 months. There was decreased glare complaints, symptoms, and dependence on correction at preoperative, 3 months, and 6 months. An increase in the level of concern and appearance from preoperative, 3 months, and 6 months post-operative was observed. Thus, an improvement in the patient's quality of life is observed three months after surgery, yet decreases slightly in six months after surgery.